Tissue‐specific analysis of Fgf18 gene function in palate development. Issue 4 (21st October 2020) - Yue, Minghui; Lan, Yu; Liu, Han; Wu, Zhaoming; Imamura, Toru; Jiang, Rulang
Abstract: Background: Previous studies showed that mice lacking Fgf18 function had cleft palate defects and that the FGF18 locus was associated with cleft lip and palate in humans, but what specific roles Fgf18 plays during palatogenesis are unclear. Results: We show that Fgf18 exhibits regionally restricted expression in developing palatal shelves, mandible, and tongue, during palatal outgrowth and fusion in mouse embryos. Tissue‐specific inactivation of Fgf18 throughout neural crest‐derived craniofacial mesenchyme caused shortened mandible and reduction in ossification of the frontal, nasal, and anterior cranial base skeletal elements in Fgf18 c/c ;Wnt1‐Cre mutant mice. About 64% of Fgf18 c/c ;Wnt1‐Cre mice exhibited cleft palate. Whereas palatal shelf elevation was impaired in many Fgf18 c/c ;Wnt1‐Cre embryos, no significant difference in palatal cell proliferation was detected between Fgf18 c/c ;Wnt1‐Cre embryos and their control littermates. Embryonic maxillary explants from Fgf18 c/c ;Wnt1‐Cre embryos showed successful palatal shelf elevation and fusion in organ culture similar to the maxillary explants from control embryos. Furthermore, tissue‐specific inactivation of Fgf18 in the early palatal mesenchyme did not cause cleft palate. Conclusion: These results demonstrate a critical role for Fgf18 expression in the neural crest‐derived mesenchyme for the development of the mandible and multiple craniofacial bones but Fgf18 expression in the palatal mesenchyme is dispensable for palatogenesis. Key Findings: The Fgf18 gene exhibits tissue‐ and domain‐specific expression during development of the mandible, tongue, and palate. Mice with neural crestspecific inactivation of Fgf18 exhibited complete penetrance of micrognathia but only 64% showed cleft palate. Maxillary explant culture assays suggested that the cleft palate defect in the neural crest‐specific Fgf18 mutant mice was secondary to other craniofacial defects. Furthermore, tissue‐specific inactivation of Fgf18 in the early developing palatal mesenchyme did not cause cleft palate. Results from this study identify multiple roles of Fgf18 in regulating craniofacial development and demonstrate that Fgf18 expression in the palatal mesenchyme is dispensable for palatogenesis.